Social and market conditions the development of physical culture and sport - Леонов [Yaroslav Leonov] Ярослав Володимирович; Васильєв [Valeriy Vasiliev] Валерій Володимирович (Slobozhanskyi Herald of Science and Sport, 2013)
Сarried out a theoretical analysis of the conditions of development of the sphere of physical culture and sports in the region. The modern conditions of functioning of the sports organizations, including the economic, socio-market indicators human development are considered. Given the generalized image of the social-market mechanism for regional management. It is showen the importance of the innovative approach to the creation of conditions for the development of the sphere of physical culture and sports at the regional level. On the basis of the system analysis of the identified problem the further ways of its solution are indicated